Nonlinear disturbance observer based spacecraft attitude control subject to disturbances and actuator faults - Yan, Ruidong; Wu, Zhong (AIP conference proceedings, 2017)
To achieve high-accuracy spacecraft attitude stabiliztion subject to complex disturbances and actuator faults, a composite controller is proposed by combining a nonlinear disturbance observer (NDO) with an adaptive integral sliding mode controller. The effects of complex disturbances and actuator faults on the spacecraft are treated as a lumped disturbance. The lumped disturbance is estimated by NDO and the estimated result is used as a feedforward compensator. The switching gain is only required to be no less than the upper bound of disturbance estimation error rather than the disturbance, and the over estimation of switching gain, caused by the initial error, is eliminated due to the global feature of the integral sliding mode item. Finally, simulations are conducted to verify the effectiveness of the proposed method.